ACL graft compression: a method to allow reduced tunnel sizes in ACL reconstruction - Lord,BR; Colaco,HB; Gupte,CM; Wilson,AJ; Amis,AA (Knee Surgery, Sports Traumatology, Arthroscopy, 2018)
PURPOSE: A common problem during ACL reconstruction is asymmetry of proximal-distal graft diameter leading to tunnel upsizing and graft-tunnel mismatch. Compression downsizing provides a graft of uniform size, allowing easy passage into a smaller tunnel. The purpose of this study was to quantify the graft compression technique and its effects on graft biomechanics and stability. It was hypothesised that compression downsizing would significantly reduce cross-sectional area (CSA); that no significant changes in graft biomechanics would occur; graft fixation stability would be improved. METHOD: Sixty-eight non-irradiated peroneus longus (PL) tendons were investigated. Twenty were halved and paired into ten four-strand grafts, 20 strands were compressed by 0.5-1 mm diameter and changes in CSA recorded using an alginate mould technique. The following properties were compared with 20 control strands: cyclic strain when loaded 70-220 N for 1000 cycles; stiffness; ultimate tensile load and stress; Young's modulus. 24 PL tendons were quadrupled into grafts, 12 were compressed and all 24 were submerged in Ringer's solution at 37 °C and the CSA recorded over 12 h. Twelve compressed and 12 control quadrupled grafts were mounted in porcine femurs, placed in Ringer's solution for 12 h at 37 °C and graft displacement at the bone tunnel aperture recorded under cyclic loading. RESULTS: Mean decreases in CSA of 31% under a stress of 471 kPa and 21% under a stress of 447 kPa were observed for doubled and quadrupled grafts, respectively. Compressed grafts re-expanded by 19% over 12 h compared to 2% for controls. No significant differences were observed between compressed and control grafts in the biomechanical properties and graft stability; mean cyclic displacements were 0.3 mm for both groups. CONCLUSIONS: No detrimental biomechanical effects of graft compression on allograft PL tendons were observed. Following compression, t